Myh10 deficiency leads to defective extracellular matrix remodeling and pulmonary disease. Issue 1 (December 2018) - Kim, Hyun-Taek; Yin, Wenguang; Jin, Young-June; Panza, Paolo; Gunawan, Felix; Grohmann, Beate; Buettner, Carmen; Sokol, Anna; Preussner, Jens; Guenther, Stefan; Kostin, Sawa; Ruppert, Clemens; et al.
Abstract Impaired alveolar formation and maintenance are features of many pulmonary diseases that are associated with significant morbidity and mortality. In a forward genetic screen for modulators of mouse lung development, we identified the non-muscle myosin II heavy chain gene, Myh10 .Myh10 mutant pups exhibit cyanosis and respiratory distress, and die shortly after birth from differentiation defects in alveolar epithelium and mesenchyme. From omics analyses and follow up studies, we find decreased Thrombospondin expression accompanied with increased matrix metalloproteinase activity in both mutant lungs and cultured mutant fibroblasts, as well as disrupted extracellular matrix (ECM) remodeling. Loss ofMyh10 specifically in mesenchymal cells results in ECM deposition defects and alveolar simplification. Notably, MYH10 expression is downregulated in the lung of emphysema patients. Altogether, our findings reveal critical roles forMyh10 in alveologenesis at least in part via the regulation of ECM remodeling, which may contribute to the pathogenesis of emphysema. Abnormal alveolar development and homeostasis are common features of pulmonary disease. Here the authors show that Myh10 expression is reduced in emphysema patients, and that Myh10 loss of function impairs alveolar formation and lung morphogenesis via upregulation of matrix metalloproteinase activity and altered matrix remodeling.